Cross-Cultural Hindrances and Ways of Overcoming Them in the Process of Communication - Harutyunyan, Narine (Armenian Folia Anglistika, 2015)
The present study aims to explore the factors that hinder the realization of cross-cultural communication. It is culture that defines the participants of communication, the choice of topics and communication strategies, the context, the way and conditions of transmitting messages, the method of encoding and decoding information, the set of communicative steps, and so on. In the process of the contact of cultures the national-specific peculiarities, unperceived during intracultural communication, become apparent. During cross-cultural contacts a clash of two worldviews talces place. In this article we make an attempt to consider the mechanisms of transformation of the vision of the world in the process of cross-cultural communication, using two contacting linguocultures as an example.